Formal institutions, human development and entrepreneurship: a comparative study between highly developed countries and member countries of the pacific alliance (2020)
In this paper a comparison is made between highly developed countries (Australia, United Kingdom, Canada, United States, Sweden, and Finland) and the four member countries of the Pacific Alliance (Colombia, Mexico, Peru and Chile), trying to find possible relationships between formal institutions, rate of entrepreneurship and human development. It is a descriptive-correlational scope study which uses information derived from the World Bank’s Governance Indicators (2018), the Heritage Foundation’s Index of Economic Freedom (2018), the Global Entrepreneurship Index (2018), and the United Nations Development Program’s Human Development Index (2018).It is concluded that there is a positive relationship between the quality of formal institutions and the level of human development in the countries that were compared.